Sense and need of evaluation of teachers performance - Fernández Franco, Francisco Javier (Avances en Supervisión Educativa, 2010)
After the evaluation-for-diagnose tests for the 2009-2010 course have been given and the results of the national evaluation-for-diagnose of the previous year -carried out by the National Institute for Evaluation- are soon to be published, it looks quite convenient to reflect on the different resources that teachers have got at their reach to improve their mission. It looks self-evident that accountability of teachers' performance is necessary. In the present article, we provide reasons for such evaluation with motivation on legal grounds and aiming at some specific ends, to conclude with a proposal for all the segments of people involved in education.